ALK‐rearranged lung cancer with intradural extramedullary spinal cord metastases responding to ceritinib treatment: A case report. Issue 8 (4th June 2018) - Xu, Yan; Zhong, Wei; Chen, Minjiang; Zhao, Jing; Wang, Mengzhao
Abstract : Intradural extramedullary spinal cord metastases in lung cancer are rarely reported, but are a disastrous event because of severe clinical symptoms and poor prognosis. Herein, we report a case of a lung cancer patient with ALK rearrangement who experienced brain, leptomeningeal, and intradural extramedullary spinal cord metastases after developing resistance to crizotinib. After ceritinib therapy, his clinical symptoms improved and magnetic resonance imaging revealed that the intradural extramedullary lesions had reduced.